Feature Extraction Technique For Text Mining Requirement For Reuse in Software Product Lines: A Systematic Literature Review - Fahmi Syuhada; Ramadhana Agung Pratama (LPPM Universitas Qamarul Huda Badaruddin, 2020)
Requirements for a system implementation can be done by feature extraction process to support the implementation process of system products. Extraction of a data or variable feature from the requirements has the effect of benefiting from Software-Product-Line. Text mining is a process of analyzing a text to generate a product. The Requirements for feature data that is processed in the text mining process can be said to be part of the Product Line Software. There are various kinds of techniques used to produce data feature requirements that enter the text mining process. This paper provides a Systematic Literature Review (SLR) of how feature extraction techniques used in the text mining data feature extraction process to support the Software Product Line process. The author uses literature search techniques to support the process of making this SLR. Besides discussing the feature extraction technique, this SLR also discusses the tools used for the Text-mining Feature Extraction process. This SLR is expected to contribute to provide a review regarding the feature of text mining data extraction techniques to support the Software Product Line process.